Examining consumer acceptance towards innovation of nutritional food waste in Malaysia - Mahmod, Razmah; Saad, Mazni; Mashahadi, Faizah; Mohamed Sayuti, Nazura (2018)
Date fruit is a type of fruit grown mainly in the eastern region. Favorable research findings on date nutritional value has led to dates becoming one of a well-known fruits consumed by many people in the world. In general, people only consume the date flesh but throw the seed as waste. Recent studies have indicated the existence of nutritional benefits in date seed with potential health benefits for human being. In relation to the promotion of green environment, this study is conducted to examine consumer acceptance towards the innovation of nutritional food by using dates seed powder as the main ingredient in producing ice-cream in Malaysia. The survey questions were adapted from Nielsen Global New Product Innovation Survey, Q1 2015 which have been distributed through the application of Google form. There were 301 respondents chosen randomly and the findings from the survey stated 94% of the respondents agreed that dates seed ice cream is an innovation food with nutritional value whereby 84.7% of the respondents are interested to buy the ice-cream if it is available in the market. The descriptive analysis indicated that the respondents accepted dates seeds ice-cream as a new flavor of ice-cream with nutritional benefits. In determining the nutrients content of the dates seed in the ice-cream mixture, the ice-cream sample was sent for chemical analysis in August 2018 at the laboratory of SIRIM QAS. The findings showed that the dates seeds ice-cream has high nutrients contents and high calories value and can be treated as substitute to coffee since it contains no caffeine.